Advance Pricing Agreement between Multinational Companies and the Government of Indonesia in the perspective of Indonesian Tax Law - Therecia Fransisca Tarigan (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
APA (Advance Pricing Agreement) is an agreement between the Directorate General of Taxes and Taxpayers and/or other country's tax authorities to agree on the criteria and/or determine the fair price or fair profit in advance of the parties who have a Special Relationship. APA generally occurs between Tax Authorities and Multinational Enterprises. The purpose of APA is to provide facilities for taxpayers to resolve transfer pricing problems. Transfer pricing is a company policy in determining the transfer price of a transaction, be it goods, services, intangible assets, or financial transactions carried out by the company. Transfer pricing is often connoted with something bad, namely a transfer of income from a company in a country with a higher tax rate to another company in a group in a country with a lower tax rate, thereby reducing the total tax burden of the group of companies. One of the challenges faced when transfer pricing occurs in Indonesia is between the Indonesian Tax Authorities and Multinational Companies. For this reason, it is necessary to take legal measures to minimize the occurrence of transfer pricing and also avoid losses to the stateKeywords: Advance Pricing Agreement, transfer pricing, Double-taxation, tax. AbstrakAPA (Advance Pricing Agreement) merupakan perjanjian antara Direktorat Jenderal Pajak dan Wajib Pajak dan/atau otoritas pajak negara lain untuk menyepakati kriteria-kriteria dan/atau menentukan harga wajar atau laba wajar dimuka para pihak yang mempunyai hubungan stimewa. APA pada umumnya terjadi antara Otoritas Pajak dengan Perusahaan Multinasional (Multinational Enterprise). Adapun tujuan dari APA ialah untuk memberikan sarana kepada Wajib Pajak guna menyelesaikan permasalahan transfer pricing. Transfer pricing merupakan kebijakan perusahaan dalam menentukan harga transfer suatu transaksi baik itu barang, jasa, harta tak berwujud, atau pun transaksi finansial yang dilakukan oleh perusahaan. Transfer pricing sering dikonotasikan dengan sesuatu yang buruk yaitu suatu pengalihan penghasilan dari suatu perusahaan dalam suatu negara dengan tarif pajak yang lebih tinggi ke perusahaan lain dalam satu grup di negara dengan tarif pajak yang lebih rendah sehingga mengurangi total beban pajak group perusahaan tersebut. Salah satu tantangan yang dihadapi apabila transfer pricing terjadi di Indonesia antara Otoritas Pajak Indonesia dengan Perusahaan Multinasional. Maka dari itu perlu adanya upaya hukum yang dilakukan untuk meminimalisir terjadinya transfer pricing dan juga menghindari terjadinya kerugian pada negara.Kata Kunci: Advance Pricing Agreement, transfer pricing, pengenaan pajak berganda, pajak